2010
DOI: 10.1097/cji.0b013e3181cc2615
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Affects CD4+ mRNA Expression and Induces Th2 Dominance in the Microenvironment of Cutaneous Squamous Cell Carcinoma in Organ Transplant Recipients

Abstract: Squamous cell carcinoma (SCC) is the most frequent cancer in organ transplant recipients (OTRs). The immune system plays a major role in the fight against SCC, however, little is known about the local inflammatory response in SCC at all. We analyzed quantity and quality of the perineoplastic inflammatory SCC microenvironment in immunocompetent patients and immmunosuppressed OTRs. RNA expression profile of SCC patients was analyzed for 8 different sets of genes relating to Th1 versus Th2 response using Gene Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…Previous studies showing that MHC class I expression and CD8 positive T cell infiltration were significantly lower in BCC than in SCC support our current result about the numerical difference of infiltrating CD8 positive T cells among BCC, BD and SCC [3,23]. Tregs infiltration was previously observed in BCC and SCC [12,15]. In those studies, the authors found that Tregs infiltration was associated with the TH2 dominant microenvironment.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies showing that MHC class I expression and CD8 positive T cell infiltration were significantly lower in BCC than in SCC support our current result about the numerical difference of infiltrating CD8 positive T cells among BCC, BD and SCC [3,23]. Tregs infiltration was previously observed in BCC and SCC [12,15]. In those studies, the authors found that Tregs infiltration was associated with the TH2 dominant microenvironment.…”
Section: Discussionsupporting
confidence: 79%
“…Expression of cytokeratins (especially CK 5/6), p63 and CAM5.2 is particularly helpful for proving the epithelial origin of spindle cell SCC. Perineural growth appears not to be more frequent in OTR, but it indicates more extensive growth and a higher risk of recurrence [4,8,9]. The peritumoral inflammatory infiltrate is significantly less intense in OTR [4].…”
Section: Epithelial Skin Neoplasmsmentioning
confidence: 99%
“…In conclusion, our study provides biomarkers of endogenous skin ageing in both females and males, which are not dependent on gender, and therefore, on the different hormone status. 1,12,7 SD 9,7 (p < 0,03),24,7 SD 15,6 (p = 0,2),46,9 SD 34,5 (p = 0,6 …”
Section: Aks10/07mentioning
confidence: 99%